Geometric complexity identifies platelet activation in familial hypercholesterolemic patients. Issue 6 (14th April 2015) - Bianciardi, Giorgio; Aglianò, Margherita; Volpi, Nila; Stefanutti, Claudia
ABSTRACT: Familial hypercholesterolemia (FH), a genetic disease, is associated with a severe incidence of athero‐thrombotic events, related, also, to platelet hyperreactivity. A plethora of methods have been proposed to identify those activated circulating platelets, none of these has proved really effective. We need efficient methods to identify the circulating platelet status in order to follow the patients after therapeutic procedures. We propose the use of computerized fractal analysis for an objective characterization of the complexity of circulating platelet shapes observed by means of transmission electron microscopy in order to characterize the in vivo hyperactivated platelets of familial hypercholesterolemic patients, distinguishing them from the in vivo resting platelets of healthy individuals. Platelet boundaries were extracted by means of automatically image analysis. Geometric complexity (fractal dimension, D ) by box counting was automatically calculated. The platelet boundary observed by electron microscopy is fractal, the shape of the circulating platelets is more complex in FH ( n = 6) than healthy subjects ( n = 5, P < 0.01), with 100% correct classification in selected individuals. In vitro activated platelets from healthy subjects show an analogous increase of D . The observed high D in the platelet boundary in FH originates from the in vivo platelet activation. Computerized fractal analysis of platelet shape observed by transmission electron microscopy can provide accurate, quantitative data to study platelet activation in familial hypercholesterolemia and after administration of drugs or other therapeutic procedures. Microsc. Res. Tech. 78:519–522, 2015 . © 2015 Wiley Periodicals, Inc.